1998
DOI: 10.1530/jrf.0.1120107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pituitary adenylate cyclase-activating polypeptide (PACAP) on progestin biosynthesis in cultured granulosa cells from rat ovary and expression of mRNA encoding PACAP type IA receptor

Abstract: The purpose of this study was to detect the presence of mRNA encoding pituitary adenylate cyclase-activating polypeptide (PACAP) (10, 100 and 1000 ng ml \m=-\ 1). At the end of the incubation period, the incubation media were collected and concentrations of progesterone, 20\g=a\-hydroxypregn-4-en-3-one (20\g=a\-OH-P)H-P) and cAMP were measured. Increasing concentrations of significantly stimulated the production of progestins (progesterone and 20\g=a\-OH-P) and cAMP accumulation in a dose-dependent mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…At the moment, we do not have a clear explanation for this; however, it might be possible that granulosa cells contain different types of PACAP receptors with varying PACAP ligand affinity. A recent study has shown the presence of PACAP type IA receptor in rat granulosa cells (Kotani et al 1998). In addition, the possible presence of PACAP type IB receptor in rat granulosa cells is supported by the work of Heindel et al (1996) who showed that PACAP38 was more effective than PACAP27 in stimulating steroidogenesis and cAMP accumulation in rat granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the moment, we do not have a clear explanation for this; however, it might be possible that granulosa cells contain different types of PACAP receptors with varying PACAP ligand affinity. A recent study has shown the presence of PACAP type IA receptor in rat granulosa cells (Kotani et al 1998). In addition, the possible presence of PACAP type IB receptor in rat granulosa cells is supported by the work of Heindel et al (1996) who showed that PACAP38 was more effective than PACAP27 in stimulating steroidogenesis and cAMP accumulation in rat granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PACAP may play an autocrine/paracrine role in the ovary. First, PACAP stimulates steroidogenesis and increases cAMP levels in cultured rat granulosa cells (Zhong & Kasson 1994, Heindel et al 1996, Kotani et al 1998. Secondly, PACAP was recently shown to accelerate meiotic maturation in follicle-and cumulus-enclosed rat oocytes (Apa et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Because the localization of PACAP is on the neuronal endings in the uterus [22] and ovary [23,24], it was suggested that PACAP, which is a novel compound with vasoactive intestinal polypeptide-like activity, may be involved in follicular growth and development [24], and may also have a functional role in the gravid uterus and placenta [25]. Other related studies on the rodent ovary also revealed associations between progesterone action and ovarian PACAP secretion [23,26]. Furthermore, the reproductive role of endometrial PACAP in deciduoma formation of rats is apparently progesteronedependent [25].…”
Section: Discussionmentioning
confidence: 99%
“…The mean levels were 154.2 ± 4.3 and 90.3 ± 5.8 in saline-treated and ethanol-treated animals, respectively. DISCUSSION PACAP stimulates cAMP production and steroidogenesis through the PAC 1 receptor, which is coupled to adenylate cyclase and phospholipase C pathways in various steroidogenic cells [12,17,24]. In particular, Rossato et al [22] clearly demonstrated that PACAP stimulates testoster-one secretion in isolated adult Leydig cells through the PAC 1 receptor.…”
Section: Inhibitory Effects Of Ethanol Treatment On Pac 1 Receptor Mrmentioning
confidence: 94%
“…Besides LH, growth hormone is reported to activate steroidogenic related enzymes and stimulate steroidogenesis in testicular Leydig cells [13]. Pituitary adenylate cyclase activating polypeptide (PACAP), like LH and growth hormone, is known to be associated with steroidogenesis in various cells, including ovarian granulosa cells, corpus luteal cells, and testicular Leydig cells [3,17,22].…”
mentioning
confidence: 99%